On Political dream teams and Financial killers: Sports Anglicisms and Metaphorical Uses in Spanish Digital Press - Lujan-García, Carmen; Núñez Nogueroles, Eugenia Esperanza (International Journal of English Studies, 2024)
The presence of English borrowings is becoming frequent in Spanish. This paper deals with the use of Anglicisms, including some cases of pseudo-Anglicisms and hybrid formations, in sports. The analysis of the digital edition of various Spanish newspapers, using the Anglicisms search tool ‘Observatorio Lázaro,’ has revealed a variety of functions that are fulfilled by these English(-looking) lexical items, such as their metaphorical uses. This study provides examples of new compound terms as well as hybrid formations and clippings, among others, some of which intend to have certain pragmatic meanings, e.g. being euphemistic or producing ironic and humorous effects on the reader. In addition, it is worth mentioning the usage of English football nicknames that seem to be getting more and more familiar to the Spanish sports audience. The orthographic inconsistency of many of the collected sport-related words is also examined and evidences the recent incorporation of these terms into Spanish.